2015
DOI: 10.1016/j.pmn.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Beliefs about Chronic Non Cancer Pain Management for Family Medicine Group Nurses

Abstract: To provide effective care for chronic pain sufferers, nurses must have a knowledge of chronic pain management. In Quebec, nurses working in Family Medicine Groups (FMGs) could play a major role in helping patients with chronic noncancer pain (CNCP); however, the extent of their knowledge about CNCP management is unknown. The primary goal of this study was to explore the knowledge and beliefs of FMG nurses about CNCP management. The secondary goal was to explore the obstacles seen by these nurses as preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
8
0
3
Order By: Relevance
“…In this respect, the results of our study corroborate those of other research showing that CE helps to increase the use of non-pharmacological approaches in the treatment of pain (Lin et al, 2008;Heinrich, Mechea, & Hoffmann, 2016). This also supports one of the recommendations of Bergeron et al (2015) suggesting that pain management CE could mitigate the lack of use of non-pharmacological approaches to treat pain.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this respect, the results of our study corroborate those of other research showing that CE helps to increase the use of non-pharmacological approaches in the treatment of pain (Lin et al, 2008;Heinrich, Mechea, & Hoffmann, 2016). This also supports one of the recommendations of Bergeron et al (2015) suggesting that pain management CE could mitigate the lack of use of non-pharmacological approaches to treat pain.…”
Section: Discussionsupporting
confidence: 89%
“…For example, we added a question about nurses' employment status and another about their work experience at Info-Santé help line and we removed all the questions pertaining to nursing practice in doctors' offices. The psychometric properties of the TPMI-F adapted for a primary care practice context (Bergeron et al, 2015) included an intraclass correlation coefficient of 0.59 for testretest reliability at a two-week interval (Bergeron et al, 2018). The content validity of this version was verified by six pain management and community health experts.…”
Section: Phase 3 Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the remarkable progress in pain management, health-care professionals continue to underestimate, under-medicate and mismanage patients in pain. [ 16 17 ] This study provides an overview of knowledge and attitude toward pain management among health-care professionals in KFHU, Al-Khobar, Saudi Arabia. It demonstrates deficient knowledge and negative attitude toward pain management among physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring <50% in attitude questions is in contradistinction to the findings reported by others in which they demonstrated that the lowest scores were mainly related to knowledge. [ 7 15 16 17 18 19 20 21 22 ] It has been suggested that the professionalization process of health-care providers reinforced negative attitudes associated with lack of enthusiasm to prescribe opioids, over concern of respiratory depression, patient addiction and drug regulatory agency sanctions. [ 23 ] We suggest that barriers to optimal pain management might be due to the deficient educational programs on pain management, which has contributed to the lack of knowledge among health-care providers over the years.…”
Section: Discussionmentioning
confidence: 99%